2011
DOI: 10.5539/ass.v8n1p62
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teenage Pregnancy on Adolescents in Amassoma Community of Southern Ijaw Local Government Area of Bayelsa State

Abstract: The study investigated the effect of teenage pregnancy among youths in Amassoma community (university town) in Southern Ijaw Local Government Area of Bayelsa State. The study adopted the descriptive survey research design involving 1000 youths. Three research questions were raised. Descriptive statistics was used to analyze the data collected. The results revealed that the age at which teenagers engage in sexual intercourse is too early, that low socio-economic status, cultural factors, permissiveness of paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This confirms the findings by Maliki (2014). Premarital sex is a taboo in the area studied, yet adolescent boys and girls indulge in it.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This confirms the findings by Maliki (2014). Premarital sex is a taboo in the area studied, yet adolescent boys and girls indulge in it.…”
Section: Resultssupporting
confidence: 90%
“…The result of which include rising incidence of female prostitution, teenage pregnancies and broken homes. According to the findings of Maliki (2014), effects and causes of teenage pregnancy include low socio-economic status, cultural factors, permissiveness of parents, drop in moral values and teenagers' sexual behaviour. The results of this study showed that teenage respondents disagreed that they could have sex because of money (48%) though 74% of the male respondents agreed that they could have sex for money.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies establish a cause-and-effect relationship between teenage pregnancy and inadequate antenatal care [ 8 – 10 ], low birth weight, and preterm birth [ 5 , 6 , 11 ]. On the hand, such a relationship is less obvious in adverse pregnancy outcomes such as preeclampsia, cesarean delivery, vaginal instrumental delivery and postpartum hemorrhage [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that pregnancy can take place as soon as a female gets to the age of puberty, with menarche (first menstrual period) normally taking place around age 12 or 13 (Onyiriuka, et al, 2012). Sixty percent (60%) of girls have their first sexual intercourse before their 13th birthday (Guttmacher Institute, 2004 andMaliki, 2012). Studies have shown that substantial numbers of teenagers have a positive or ambivalent attitude towards pregnancy (Jaccard et al, 2003, Condon et al, 2001, Stevens-Simon et al, 1996.…”
Section: Effects Of Age At First Birthmentioning
confidence: 99%